Analisis Kinerja Keuangan PT. Gudang Garam TBK Tahun 2020-2023 - Sam, Nursyamsih Husma; Goso, Goso; Halim, Muh. (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to determine the analysis of the Company’s financial performance. The method in this research is quantitative descriptive analysis method. The population used the financial statements of PT Gudang Garam Tbk, and the sample is the company’s financial statements in the form of profit and loss statements and balance sheets. This type of research is comparative research. Based on the results of the analysis obtained, namely the profitability ratio from 2020 to 2022 has decreased, gross profit margin that in 2020 the level of efficiency in controlling cost of goods was 15.1%, in 2021 there was a significant decrease to 11.4% and in 2022 there was also a decrease of 8.8%, return in investment is known that in 2020 9.7% and in 2021 the ROI value is 6.2% and in 2022 it is 3.2%, it can be seen that the decline is very drastic from year to year. The liquidity ratio from 2020 to 2022 has decreased. Current Ratio from 2020 to 2022 decreased by 824% and in 2021 there was a decrease to 596% as well as in 2022 there was also a decrease with a value of 552%. The quick ratio was 160.5% and in 2021 it decreased by 119% as well as in 2022 by 78%. Solvency from 2020 to 2022 there was an increase in the Debt to Asset Ratio of 25.1 and in 2021 and 2022 there was an increase in the ratio value of 34.0 and 34.6. Debt to equity ratio is known in 2020 amounting to 33.6 and in 2021 amounting to 51.7 while in 2022 amounting to 53.0 there was a significant increase between the time frame 2020 to 2022.